Engineering a genome‐reduced bacterium to eliminate Staphylococcus aureus biofilms in vivo. Issue 10 (6th October 2021) - Garrido, Victoria; Piñero‐Lambea, Carlos; Rodriguez‐Arce, Irene; Paetzold, Bernhard; Ferrar, Tony; Weber, Marc; Garcia‐Ramallo, Eva; Gallo, Carolina; Collantes, María; Peñuelas, Iván; Serrano, Luis; Grilló, María‐Jesús; et al.
Abstract: Bacteria present a promising delivery system for treating human diseases. Here, we engineered the genome‐reduced human lung pathogen Mycoplasma pneumoniae as a live biotherapeutic to treat biofilm‐associated bacterial infections. This strain has a unique genetic code, which hinders gene transfer to most other bacterial genera, and it lacks a cell wall, which allows it to express proteins that target peptidoglycans of pathogenic bacteria. We first determined that removal of the pathogenic factors fully attenuated the chassis strain in vivo . We then designed synthetic promoters and identified an endogenous peptide signal sequence that, when fused to heterologous proteins, promotes efficient secretion. Based on this, we equipped the chassis strain with a genetic platform designed to secrete antibiofilm and bactericidal enzymes, resulting in a strain capable of dissolving Staphylococcus aureus biofilms preformed on catheters in vitro, ex vivo, and in vivo . To our knowledge, this is the first engineered genome‐reduced bacterium that can fight against clinically relevant biofilm‐associated bacterial infections. Synopsis: A non‐pathogenic strain of Mycoplasma pneumoniae is engineered to express biofilm dispersing agents as well as bactericidal peptides against Staphylococcus aureus . The engineered strain efficiently dissolves S. aureus biofilms in vitro and in vivo . Mycoplasma pneumoniae offers unique features that might be of interest for a bacterial‐based therapeutic vector. Here, an attenuated version of this bacterium is generated after studying the role of different pathogenic factors. Using strong synthetic promoters and native secretion signals, a genetic platform is designed coding for antibiofilm and bactericidal enzymes. In vitro, ex vivo and in vivo studies confirmed the ability of the engineered M. pneumoniae strain to efficiently dissolve S. aureus biofilms. Abstract : A non‐pathogenic strain of Mycoplasma pneumoniae is engineered to express biofilm dispersing agents as well as bactericidal peptides against Staphylococcus aureus . The engineered strain efficiently dissolves S. aureus biofilms in vitro and in vivo .